SQ3R Method and Its Implications on the Reading Skills of English Language Students in Adamawa State Polytechnic Yola, Nigeria - Akinkurolere, Susan Olajoke; Usman, Baba Jimeta (Islamic University Multidisciplinary Journal, 2019)
Reading as a basic literacy skill has continuously been referred as one of the factors responsible for students’ performance in schools. The attraction to enhancing reading skills among students calls for unceasing research. Therefore, the study investigated reading proficiency and comprehension among English language students in selected departments in Adamawa State Polytechnic, Yola, Nigeria. Two departments were selected purposively selected for the study. Also, the departments chosen were with population above one hundred. This research was guided by Schema theory. Indeed, the ability to read efficiently in English is an essential skill in all spheres of life. Moreover, the effects of reading proficiency on comprehension was examined to achieve the objective through the employment of the SQ3R method for reading texts. An extract of a comprehension passage served as a research instrument for the purpose of pre-test and post-test in the study. The findings revealed that students from both departments performed inadequately before the intervention. Also, there was significant improvement after applying SQ3R method of teaching reading. The study recommended the application of SQ3R as an effective method in enhancing reading proficiency and comprehension in tertiary institutions in Nigeria.
Keywords: Tertiary institution; Reading; Proficiency; Comprehension; SQ3R